Synthesis and Characterization of Some New 1,2,3-Triazole, Pyrazolin-5-one and thiazolidinone Derivatives - Hassan, Huda Ahmed (Al-Nahrain Journal of Science, 2013)
Five membered heterocyclics derivatives were synthesized in this work by three routes. The first route includes the synthesis of N-benzoic acid 1,2,3,-triazole derivatives (3),(4) by diazotation of methyl-2-amino benzoate and treating the resulted salt (1) with sodium azide and ethyl acetoacetate or acetyl acetone, respectively. In the second route, derivatives of pyrazole (8) pyrazolin-5-one (9), (10) were prepared by the reaction of the salt (1) with some active methylene compounds to give the corresponding hydrazones derivatives (5-7) which then they were treated with hydrazine hydrate. The third route afforded the synthesis of three derivatives (12), (15a), (15b) of thiazolidinone by two different methods. AII compounds were confirmed by their melting points, FTIR, U.V-vis spectra and 1 H-NMR spectra for some of them.